2003
DOI: 10.1124/mol.63.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Relating Neuronal Nicotinic Acetylcholine Receptor Subtypes Defined by Subunit Composition and Channel Function

Abstract: Neuronal nicotinic acetylcholine receptors (nAChRs) are widespread, diverse ion channels involved in synaptic signaling, addiction, and disease. Despite their importance, the relationship between native nAChR subunit composition and function remains poorly defined. Chick ciliary ganglion neurons express two major nAChR types: those recognized by ␣-bungarotoxin (␣Bgt), nearly all of which contain only ␣7 subunits (␣7-nAChRs) and those insensitive to ␣Bgt, which contain ␣3, ␣5, ␤4, and, in some cases, ␤2 subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 38 publications
3
56
0
1
Order By: Relevance
“…The observation that the -chain-deficient TCR/ CD3 complex is ineffective in transmitting signals to raise [Ca 2ϩ ] i in response to nicotine further supports this inference. ␣-BTX and MLA are considered relatively specific antagonists of ␣7-nAChRs and block nicotine-induced currents in neuronal cells (16). However, contrary to their action in PC12 cells, both ␣-BTX and MLA stimulated a strong Ca 2ϩ response in T cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The observation that the -chain-deficient TCR/ CD3 complex is ineffective in transmitting signals to raise [Ca 2ϩ ] i in response to nicotine further supports this inference. ␣-BTX and MLA are considered relatively specific antagonists of ␣7-nAChRs and block nicotine-induced currents in neuronal cells (16). However, contrary to their action in PC12 cells, both ␣-BTX and MLA stimulated a strong Ca 2ϩ response in T cells.…”
Section: Discussionmentioning
confidence: 98%
“…In mammals, these receptors are also widely expressed in nonexcitable cells such as keratinocytes (12), lung type-2 epithelial cells (13,14), and macrophages (15), but their structure and function on non-neuronal cells are not clearly defined. Although in neurons, the ␣7-nAChRs participate in neurotransmission which is blocked by ␣-bungarotoxin (␣-BTX) and methyllycaconitine (MLA) (16,17), it is unlikely that these receptors perform such a function in nonexcitable cells. Chronic in vivo nicotine treatment suppresses the immune and inflammatory responses (18 -20), causing T cell anergy (21) and decreased leukocyte migration; however, acute exposure to nicotine increases intracellular calcium [Ca 2ϩ ] i and cell migration in several cell types (18,14,22,23).…”
Section: T He Nicotinic Acetylcholine Receptors (Nachrs)mentioning
confidence: 99%
“…2, A and B). Further analysis with selective blockers of nAChR subunits revealed that ␣-conotoxin AulB (10 M; conotoxin), an inhibitor of ␣ 3 containing nAChRs, (14,22), reduced the nicotine-evoked increase in [Ca 2ϩ ] i by ϳ60% (P Ͻ 0.001), whereas methyllcaconitine (50 nM), a selective inhibitor of ␣ 7 -nAChRs (30), caused a modest (24%) but significant attenuation of the [Ca 2ϩ ] i response to nicotine (P Ͻ 0.05; Fig. 2, A and B).…”
Section: Effect Of Ih On Nachrs Expression In Amcmentioning
confidence: 99%
“…icotinic acetylcholine receptors (nACh-Rs) belong to a family of ligand-gated channels that form a cationselective pathway across the plasma membrane of a given cell (1) and consist of hetero-or homopentamers of 17 different ␣-, ␤-, ␥-, ␦-, and ⑀-subunits that determine the properties of the channel (2,3). They are implicated in neuronal processes such as synaptic transmission but also in the regulation of neuronal cell death in response to injuries such as hypoxia and glutamate excitotoxicity (4) and, outside the central nervous system, in the modulation of peripheral inflammation (5,6).…”
mentioning
confidence: 99%